Just Sustainability in the Global South: A Case Study of the Megacity of Dhaka. Issue 4 (December 2018) - Ahmed, Saleh; Meenar, Mahbubur
Dhaka, the capital city of Bangladesh, accommodates 18 million people and is one of the largest megacities in the world. A large share of its population is poor and lives in informal settlements which can be called slums. In addition to precarious and unhealthy living conditions, these slum dwellers lack formal land tenure rights and therefore are subject to government-supported evictions. Slum evictions due to various urban development pressures may bring short-term benefits to the urban real estate market but have adverse long-term effects on sustainability and livelihoods of the city's poor residents. Using the conceptual lens of just sustainability (JS)—which facilitates an investigation of the normative and practical challenges of sustainability and environmental justice—the authors argue that urban development in Dhaka needs to ensure social justice and sustainability. While the geographic focus of this article is Dhaka, this study has direct relevance—in terms of policy and planning implications—for other cities in the Global South.